Better Living by Their Own Bootstraps : Black Women's Activism in Rural Arkansas, 1914-1965 - Jones-Branch, Cherisse (Book collections on Project MUSE., 2021)
"Better Living by Their Own Bootstraps is the first major study to consider Black women's activism in rural Arkansas. The text explores Arkansas's rural history to foreground Black women's navigation of racial and gender politics as a means to uplift African Americans, develop opportunities for social mobility, and subvert the formidable structures of white supremacy during the Jim Crow years"--